Earmarked Taxation: Welfare versus Political Support - Dieter Bös (Center for Economic Studies and ifo Institute (CESifo), 1999)
Compared with the traditional public-finance approach of a monolithic fully informed planner, earmarking of taxation is less likely to be optimal if a principal-agent setting is considered, where taxing and spending are performed by two separate agents which are monitored by the parliament. We assume that the parliament either maximizes welfare or expected votes. Vote maximizers are more inclined to choose earmarking, but at the price of inefficiently high costs.
Keywords: 330; Earmarking; efficient taxation; asymmetric information